Treatment patterns among elderly patients with stage IV breast cancer treated with HER-2-targeted therapy. (September 2014) - Lang, Kathleen; Hao, Yanni; Huang, Huan; Lin, Iris; Rogerio, Jaqueline Willemann; Menzin, Joseph
Aim: To evaluate treatment patterns among elderly, newly diagnosed stage IV breast cancer patients receiving HER-2-targeted therapy.Methods: Women aged 65+ with an incident diagnosis of stage IV breast cancer (index) and no history of other cancer were identified from 2006 to 2010 linked Surveillance, Epidemiology and End Results and Medicare data. Continuous enrollment from 1 year preindex (baseline) through disenrollment, death or the end of the data (follow-up) was required. Patients were required to receive HER-2-targeted therapy (trastuzumab or lapatinib) during follow-up. Treatment therapies during follow-up were evaluated, as was the distribution of treatment combinations. Initial treatment regimens were evaluated based on the treatment(s) received after index. A 42-day gap in therapy or the addition of a biologic therapy was used as a marker for a subsequent regimen.Results: A total of 173 patients were identified (mean [standard deviation] age: 73.9 [6.7] years). The majority received trastuzumab (>93%) during follow-up (mean [standard deviation] duration: 24.3 [11.3] months), with 9.8% receiving lapatinib. Most received chemotherapy (83.2%), approximately half received surgery (55.5%), over 40% received hormonal therapy and a third received radiation (35.3%). Trastuzumab + chemotherapy was the most common initial treatment regimen (43.9%); less common therapies include trastuzumab alone (17.3%), and trastuzumab + chemotherapy + hormonal (13.3%). Among patients receiving chemotherapy, the majority received a taxane-based chemotherapy. The average treatment duration for any treatment regimen was just less than a year (44.9–52.5 weeks).Conclusion: Among this population, the majority received taxane-based combination chemotherapy, consistent with National Comprehensive Cancer Network guidelines.